Topological, metric and fractal properties of probability distributions on the set of incomplete sums of positive series - Pratsiovytyi, M.V.; Feshchenko, O.Yu. (Інститут математики НАН України, 2007)
We study the structure, topological, metric and fractal properties of the distribution of random incomplete sum of the convergent positive series with independent terms under certain conditions on the rate of convergence of series and on the distributions of its terms. We also study the behaviour of the absolute value of the characteristic function of this random variable at infinity and the fractal dimension preservation by its distribution function.